Treatment of Periprosthetic Joint Infection and Fracture-Related Infection With a Temporary Arthrodesis Made by PMMA-Coated Intramedullary Nails – Evaluation of Technique and Quality of Life in Implant-Free Interval - Walter, Nike; Baertl, Susanne; Lang, Siegmund; Szymski, Dominik; Weber, Johannes; Alt, Volker; Rupp, Markus (Frontiers in Surgery, 2022)
Background Antimicrobial coating of intramedullary nails with polymethyl methacrylate (PMMA) bone cement promises infection control and stabilization for subsequent bone healing. However, when removing the implant, bone cement can debond and remain in the medullary cavity of the long bones, representing a nidus for reinfection. This work presents a technique comprising reinforcement of PMMA-coated intramedullary nails with cerclage wire to prevent such problems in patients treated for fracture-related infection (FRI) or knee periprosthetic joint infection (PJI) with a static spacer as temporary arthrodesis allowing weight-bearing in the implant-free interval. Outcomes of this surgical treatment were evaluated in terms of (i) associated complications and (ii) patient-reported quality of life. Methods In this retrospective case series, 20 patients with PJI (n = 14, 70%) and FRI (n = 6, 30%) treated with PMMA-coated intramedullary nails reinforced with cerclage wire between January 2021 and July 2021 were included. Quality of life during the implant-free interval was evaluated with the EQ-5D, SF-36, and an ICD-10 based psychological symptom rating and compared with previously analyzed cohorts of successfully treated PJI and FRI patients in whom eradication of infection and stable bone consolidation was achieved. Results Complications during the implant-free interval comprised a broken nail in one case (5.0%) and a reinfection in one case (5.0%). Coating-specific side effects and cement debonding during removal did not occur. The mean physical health component score of SF-36 was 26.1 ± 7.6, and the mean mental health component score reached a value of 47.1 ± 18.6. The mean EQ-5D index value was 0.36 ± 0.32 and the mean EQ-5D visual analogue scale rating was 47.4 ± 19.4. The scores were significantly lower than those in the successfully treated FRI cohort but not in the PJI cohort. The mean ICD-10-based symptom rating scores revealed psychological symptom burden on the depression scale and enhanced levels of anxiety in comparison with healed FRI and PJI patients. Conclusion Reinforcement of PMMA bone cement-coated implants seems to be a reasonable treatment option to create a temporary arthrodesis, preventing detachment of the bone cement when the implant was removed. Level of Evidence: IV.